Penggambaran perpustakaan dan pustakawan dalam role playing game Genshin Impact - Qoonitah Amiza Rahma; Nina Mayesti (Perpustakaan Universitas Gadjah Mada, 2023)
Introduction. This study discusses reception analysis regarding the depiction of libraries and librarians in the role-playing game (RPG) Genshin Impact, particularly House of Daena as the most extensive library and Lisa as the librarian at the Knights of Favonius Library. Through Genshin Impact, the description of libraries and librarians is examined through a different approach from research in other media. Data Collection Methods. This study use a qualitative method with a reception study approach. The data collection techniques with in-depth interviews was conducted using a purposive sampling technique with five informants. Data Analysis. The data is analyzed by reducing, presenting data, and drawing conclusions. Results and Discussion. The results showed that (1) the informant, as a player, had the view that the Knight of Favonius Library and House of Daena the same as library in real world; and (2) Lisa and Katayoun, as librarians, described as more friendly and professional than the real librarians. Conclusion. The depiction of libraries and librarians in Genshin Impact presents a positive impression that is expected to improve the views of library users in the real world.